Sleep-disordered breathing is associated with blood pressure and carotid arterial stiffness in obese children. Issue 1 (January 2017) - Tagetti, Angela; Bonafini, Sara; Zaffanello, Marco; Benetti, Maria V.; Vedove, Francesco Dalle; Gasperi, Emma; Cavarzere, Paolo; Gaudino, Rossella; Piacentini, Giorgio; Minuz, Pietro; Maffeis, Claudio; Antoniazzi, Franco; et al.
Abstract : Introduction: Both sleep-disordered breathing (SDB) and high blood pressure (BP) occur more frequently among obese children than among normal weight children, and this may be due to endothelial dysfunction and worsened arterial stiffness. The aim of this study was to evaluate the possible association between SDB and BP, and the possible role of endothelial function and local and systemic arterial stiffness in a sample of obese children asymptomatic for sleep disturbances. Materials and methods: Thirty-nine obese children were included in the study. Children underwent overnight limited channel polysomnography, and the vascular measurements included the following: office and 24-h ambulatory BP; brachial flow-mediated dilatation, carotid intima–media thickness and carotid distensibility measured using ultrasound; and systemic arterial stiffness index measured using digital volume pulse analysis. Results: Significant correlations between different BP measurements (both office and ambulatory BP monitoring and estimated by Z score) and SDB were found, including correlations involving the respiratory disturbance index, the apnea–hypopnea index (AHI), the number of desaturations per hour and the mean peripheral saturation ( r ranging between 0.330 and 0.474). Carotid distensibility was correlated with the AHI ( r  = −0.367; P  = 0.030) and with the mean oxygen saturation ( r  = 0.401; P  = 0.017). In contrast, there was no relationship among flow-mediated dilatation, stiffness index, carotid intima–media thickness and all the tested respiratory markers. In the multivariate analysis, the supine Z SBP remained independently associated with the number of desaturations per hour and the AHI, even after correction for carotid distensibility and BMI. Conclusion: Our data suggest that in obese children asymptomatic for sleep respiratory problems, SDB might worsen BP, in part, through an increase in arterial stiffness. Abstract : Supplemental Digital Content is available in the text